2020
DOI: 10.2147/ijwh.s283122
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence-Proportion of Maternal Near-Misses and Associated Factors in Southwest Ethiopia: A Prospective Cross-Sectional Study</p>

Abstract: Background: Pregnancy-related morbidity and mortality continue to have a serious impact on the lives of women all over the world. Women in sub-Saharan Africa accounted for nearly two-thirds of global maternal deaths. The World Health Organization recommends monitoring maternal near-miss provides better information regarding the quality of maternal health care, on which to base action to prevent further death. Accordingly, this study sought to assess the incidence-proportion of maternal near-miss and its risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
5
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 24 publications
2
15
5
9
Order By: Relevance
“…14 A study in Southwest Ethiopia found that the odds of maternal nearmisses among multiparous women were 2.5 times that of nulliparous women. 15 Cesarean mode of delivery was significantly associated with a risk of undergoing an emergency peripartum hysterectomy in our sample of women in Malawi. Seventy-six percent of our cohort delivered via cesarean.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…14 A study in Southwest Ethiopia found that the odds of maternal nearmisses among multiparous women were 2.5 times that of nulliparous women. 15 Cesarean mode of delivery was significantly associated with a risk of undergoing an emergency peripartum hysterectomy in our sample of women in Malawi. Seventy-six percent of our cohort delivered via cesarean.…”
Section: Discussionmentioning
confidence: 72%
“… 14 A study in Southwest Ethiopia found that the odds of maternal near-misses among multiparous women were 2.5 times that of nulliparous women. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Rev enferm UERJ, Rio de Janeiro, 2022; 30:e65125 p.5 Nos 12 estudos que compuseram a revisão, foram identificados fatores sociodemográficos associados à ocorrência de NMM, envolvendo possuir menor grau de escolaridade 2,5,12-15 , residir no interior ou em área rural 2,14,20 , ter baixa renda 2,12-14,21 e ser extremos de idade 5,12,15,21 ; e obstétricos, com destaque para cesariana prévia 9,18,19 ou na gestação analisada 2,5,16,18,21 , aborto anterior 13,21 , primiparidade 15,19 e falhas na atenção pré-natal 2,13,18,19,21 .…”
Section: Resultsunclassified
“…Como fatores clínicos e obstétricos relacionados à ocorrência de NMM, destacam-se as seguintes complicações obstétricas: os distúrbios hipertensivos, que apareceram em 10 dos 12 estudos desta revisão 2,5,12,13,[15][16][17][18][19]21 ; as complicações hemorrágicas, em nove estudos 2,5,12,13,15-20 ; a sepse, mencionada em cinco estudos 2,12,[17][18][19] ; e o histórico gestacional de anemia, relatado em quatro artigos 12,14,18,20 . Nos fatores clínicos maternos preexistentes, foram evidenciadas doenças crônicas, como a hipertensão 14,18 .…”
Section: Resultsunclassified
See 1 more Smart Citation